2022
DOI: 10.3390/v14020279
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Chest CT Abnormalities and Clinical Features in Patients with the Severe Fever with Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by the SFTS virus. It involves multiple organ systems, including the lungs. However, the significance of the lung involvement in SFTS remains unclear. In the present study, we aimed to investigate the relationship between the clinical findings and abnormalities noted in the chest computed tomography (CT) of patients with SFTS. The medical records of 22 confirmed SFTS patients hospitalized in five hospitals in Nagasaki, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The present study revealed that SFTS and JSF did not differ in patients' underlying conditions; however, many symptoms, such as altered mental status and diarrhea were more frequently found in patients with SFTS. These symptoms may be associated with viremia in SFTS [30,31]. Skin rash and tick bite were frequently found in patients with JFS.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The present study revealed that SFTS and JSF did not differ in patients' underlying conditions; however, many symptoms, such as altered mental status and diarrhea were more frequently found in patients with SFTS. These symptoms may be associated with viremia in SFTS [30,31]. Skin rash and tick bite were frequently found in patients with JFS.…”
Section: Discussionmentioning
confidence: 96%
“…All definitions used in the study were established before the data analyses. An episode of SFTS was defined as SFTSV, in which viral RNA was confirmed by real-time PCR analysis of a serum sample, as previously described [31]. The diagnosis of JSF was defined as either a 4-fold increase in immunoglobulin G (IgG) in the serum sample with immunofluorescence assay, PCR analysis of a blood sample, or tissue biopsy (eschar) [32].…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…SFTSV infection can elicit damage to multiple organ systems including lung. It was reported that lung imaging abnormalities was present in 29 to 68.1% of SFTS patients [41]. Pulmonary infection was associated with fatality or increased disease course in SFTS patients [42].…”
Section: Discussionmentioning
confidence: 96%